Determinación de la calidad del agua mediante bioindicadores, análisis físico-químico y microbiologicos de la laguna Santo Domingo del Parque Nacional Cotopaxi, provincia de Pichincha, periodo 2018. - Ceballos Peñafiel, Karen Nathali (2018)
The present investigation was carried out in the Cotopaxi National Park, in the sector belonging to the Mejía canton of Pichincha province, in the Laguna Santo Domingo, in order to determine the index of water quality, through bioindicators and physical-chemical analysis, and microbiological. For the water evaluation quality indices using bioindicators, samples were taken in April, May and June at five sampling points and the identification techniques by tolerance (EPT) Ephemeroptera, Plecoptera, Trichoptera, ( BMWP / Col.) Biological Monitoring Working Party, (ABI) Andean Biotic Index, (IBF) Biotic Index of Families and for the physical, chemical and microbiological analysis, the ICA DINIUS - NFS (National Sanitation Foundation) were applied, where samples were from the main entrance and exit of the lake body in the months of April and June. The obtained results by applying the ICA. NFS and ICA. DINIUS, determined that the water conditions are: bad and / or polluted, where the parameters were compared with the Ecuadorian Legislation in Force - TULSMA, Book VI, Annex I, with Table 10. At the same way, when were applyed techniques of the BMWP / Col. indexes, and ABI, it was defined that the water nature lime corresponds to waters in doubtful and / or critical conditions, that says is very polluted water. The IBF indicates that the body of water has an excellent index, therefore, it is determined that Laguna Santo Domingo does not show apparent organic contamination